Características anatômicas e fisiológicas foliares e crescimento de Typha domingensis Pers. submetida à diferentes disponibilidades hídricas - Cruz, Yasmini da Cunha (2017)
Aquatic macrophytes show great plasticity denoting tolerance to a diversity of environmental conditions. Variations in the availability of water in natural aquatic ecosystems are conditioned, mainly, by the climate. Climate change has produced instability in the climate by altering the temperature and rain periods, thus, water supply in some regions is declining resulting in periods of drought. The present study was carried out to evaluate the anatomical and physiological leaf characteristics in Typha domingensis that denote tolerance to reduced water availability. Acclimated clones of T. domingensis produced in a greenhouse were standardized for size and transferred to pots with 2.4L of vermiculite that contained nutrient solution. Different substrate saturation levels were used for 60 days: waterlogged, 100%, 75%, 50%, and 25% of field capacity of the substrate. Leaf anatomical characteristics were analyzed by light microscopy and for gas exchange levels, chlorophyll content, and leaf water potential, and at the end of the experiment, growth was evaluated. Plants submitted to waterlogged and 100% of the field capacity conditions presented similar capacity to produce new plants; in 75% and 50% conditions, this capacity was reduced, but there was population growth. Under 25% conditions, all the individuals died. Plant height and leaf area were proportionally reduced with the lower availability of water, compared to waterlogged plants. Likewise, photosynthesis and total transpiration, as well as the efficient use of water, were reduced during water restriction. Leaf water potential reduced to 75% and 50% of the field capacity. The stomatal density reduced in the abaxial and adaxial faces in treatments with reduced water availability in relation to the flooded plants. Meanwhile, the thickness of the palisade parenchyma was only reduced in the abaxial face in the treatment with 50% of the field capacity. The reduction of photosynthesis in T. domingensis plants is related to the decrease of leaf area. T. domingensis is tolerant to 50% water reduction in the substrate; however, 25% water reduction limits its survival.